Development of an equatorial carbonate platform across the Triassic-Jurassic boundary and links to global palaeoenvironmental changes (Musandam Peninsula, UAE/Oman) - Honig,M; John,C; Manning,C (Gondwana Research, 2016)
TheTriassic-Jurassicboundaryismarkedbyoneofthe‘bigfive’massextinctionsofthePhanerozoic.Thisboundaryeventwasaccompaniedbyseveralcarboncycleperturbations,potentiallyinducedbytheopeningoftheCentralAtlanticandassociatedvolcanism,andaccompaniedbyanoceanacidificationevent.Continuouscarbonatesuccessionscoveringthisintervalofenvironmentalchangearehoweverrare.Heredatafromashallow-marineequatorialmixedcarbonate-siliciclasticsuccessionispresented,thatwasstudiedonaregionalscale.Foursectionsthatare48kmapartwereexaminedontheMusandamPeninsula(UnitedArabEmiratesandSultanateofOman).Thesystemwasanalysedforitssedimentology,verticalandlateralfacieschanges,andstablecarbonandoxygenisotopes.StrontiumisotopeanalysiswasusedtodeterminethepositionoftheTriassic-Jurassicboundaryhorizon.ThestudiedrampexperiencedanepisodeofdemiseduringtheLateTriassic,followedbyarestrictedmicrobialitedominatedramp,containinglargeamountsofsiliciclasticfacies.DuringtheLatestTriassicthediversecarbonatefactoryrevivedandflourishedacrosstheTriassic-Jurassicboundary.NoclearevidenceforabiocalcificationcrisisoranoceanacidificationeventacrosstheTriassic-Jurassicboundaryisvisible.Lateralfaciesheterogeneitiescanbeobservedacrossthestudiedinterval,attributedtohydrodynamicactivity,includingtropicalstorms,crossingtheextensiveshelfarea.Althoughevidenceforsynsedimentarytectonicactivityispresent,theverticalstackingpatternislargelycontrolledbychangesinrelativesealevel.Therefinedchronostratigraphyaccompaniedbythedetailedenvironmentofdepositionanalysisallowsforarefinementoftheregionalpalaeogeography.TheneriticequatorialcarbonateramphasarchivedanegativecarbonisotopeexcursionprecedingtheTriassic-Jurassicboundarythathasalsobeenreportedfromotherstudysites.ThelackofevidenceforabiocalcificationcrisisacrosstheequatorialTriassic-JurassicboundaryindicatesthattheTethysdidnotexperienceadistinctglobalacidificationevent.